Sleeping Beauty? A Prospective Study on the Prevalence of Sleep Problems and Their Potential Determinants in Professional Dancers - Astrid Junge; Rogier M. van Rijn; Janine H. Stubbe; Anja Hauschild (Sports Medicine - Open, 2024)
Abstract Background Sleep is important for health and performance but has rarely been studied in professional dancers. The aim was to analyse the prevalence of sleep problems in professional dancers and their potential determinants at the beginning of and during the season. Methods Professional dancers of six German companies answered a comprehensive baseline questionnaire on physical and mental health, including the Sleep Difficulty Score of the Athletic Sleep Screening questionnaire (ASSQ-SDS) in the beginning of the season and weekly health reports during the season. Numerical rating scales were used for severity of poor sleep, musculoskeletal pain, being stressed/overloaded, all health problems, impaired ability to dance, and workload in the previous seven days. Results Of the 147 dancers who answered the baseline questionnaire, 104 (70.7%) completed in total 3186 weekly health reports (response rate: 71.2%). In the beginning of the season 53% of the dancers reported sleep problems of mild (34.0%), moderate (13.6%) or severe extent (5.4%), without differences between sexes, age groups, ranks of the dancers, company sizes or dance styles. The average weekly prevalence of “poor sleep” during the season was 68.8%. Multivariate regression analyses showed that symptoms of depression were significant determinants of sleep problems and the rating of “poor sleep” at baseline; while musculoskeletal pain, being stresses/overloaded, all health problems, impaired ability to dance, and physical and mental workload were significant determinants of “poor sleep” during the season. Variables of the baseline questionnaire were not significantly related to the individual mean rating of “poor sleep” during the season, except of the quality and duration of sleep. Conclusion Sleep problems are frequent in professional dancers and related to their physical and mental health and workload. An assessment of sleep should be part of routine health screenings and interventions to improve sleep should be implemented, especially for dancers with pre-existing sleep problems and for periods of high workload.